Energy-efficient optimization algorithm based on vertical beamforming for 3D MIMO-OFDMA system - Ting LI; Linjie QIU; Wei JI (Dianxin kexue)
An energy-efficient optimization algorithm was proposed for the 3D MIMO-OFDMA communication system.The proposed algorithm based on vertical beamforming technology maximized energy efficiency by adjusting the resource allocation,power allocation and the downtitles of the beam.According to the theory of fractional optimization,the complex fractional optimization problem could be converted into a more tractable integral optimization problem.The lagrangian operator was introduced to obtain the optimal value of energy efficiency by iteration.Simulation results show that the proposed algorithm can achieve higher energy efficiency with fewer iterations.